Foot Exercise Movement Activities as Efforts to Lower Blood Sugar Levels in Diabetes Mellitus Patients - Akas Yekti Pulih Asih; Budhi Setianto; Agus Aan Adriansyah; Iftitahurrohmah Iftitahurrohmah; Sofia Nur Islami; Ahla Tamaro (Universitas Muhammadiyah Sidoarjo, 2021)
Based on Riskesdas in 2018, the prevalence of diabetes mellitus in Indonesia based on interviews showed an increase from 1.1 percent (2007) to 2.1 percent in 2019. The International Diabetes Federation (IDF) estimates that DM sufferers in Indonesia in 2020 will amount to 178 million people aged over 20 years and assuming a DM prevalence of 4.6%, 8.2 million DM patients will be obtained. The most data on visits from internal medicine policymakers at the outpatient clinic of Islamic Hospital in Surabaya were diabetes militus. One of the most common complications of diabetes mellitus is diabetic foot, which can manifest as ulcers, infections and gangrene and Charcot's arthropathy. The method used in this community service activity is carried out to increase knowledge and understanding of public awareness by doing foot exercises to reduce sugar levels. This community service activity is carried out by educating patients with diabetes at the Internal Medicine Department of the Islamic Hospital Surabaya. Diabetes exercise carried out by the GLC group which was carried out independently by the participants showed an average decrease in sugar levels with an average of 12.5 points with participants who routinely did regular exercise 4 times a week showing the largest number of points of decline. Sig. (2-tailed): Probability value / p value Paired T test: Result = 0.000 shows that there is a difference between before and after treatment. Implementation of diabetic foot exercises which were carried out independently at home by GLC patient at Surabaya Islamic Hospital A Yani